Avalia????o de um programa de reabilita????o pulmonar domiciliar em pacientes com doen??a pulmonar obstrutiva cr??nica - Nascimento, Eloisa Sanches Pereira do (2013)
Chronic obstructive pulmonary disease (COPD) is a respiratory disease characterized by chronic airflow limitation that leads, in addition to pulmonary impairment, the significant systemic effects. Characterized by pulmonary and systemic inflammation, shows increases in plasma levels of inflammatory cytokines even in stable disease. Pulmonary rehabilitation (PR), a multidisciplinary program of physical exercise and education, improves exercise capacity, quality of life and reduces breathlessness. The aim of this study was to evaluate whether a Home-based PR program improves exercise tolerance in patients with COPD, as well as the quality of life and systemic inflammation. This prospective study was conducted at the Laboratory of Functional Assessment of Respiratory - UNINOVE. After anamnesis, patients were subjected to evaluations of: quality of life and dyspnea, spirometry, respiratory muscle strength, upper limbs incremental test, incremental shuttle walk test, bioelectrical impedance analysis and quantification of systemic inflammatory markers (IL-6 and IL-8). Patients received at the end of reviews, a primer containing the physical exercises to be performed in the home, 3 times per week for 8 consecutive weeks. We evaluated 25 patients, and 14 completed the pre and post reviews Home-based PR program. After the intervention there was a significant increase in the walking distance the maximal inspiratory pressure, improvement in 2 components of quality of life questionnaire and decreased plasma levels of IL-8. The Home-based PR program improves exercise tolerance, inspiratory muscle strength, quality of life and systemic inflammation in COPD patients.